Preeclampsia correlates with maternal and perinatal outcomes in Regional Public Hospital, Madiun, Indonesia - Fadhila Anindya Putri Ariyan; Eko Gunawan Sukowati; Widi Fatmawati (Majalah Obstetri dan Ginekologi, 2022)
HIGHLIGHTS 1. Preeclampsia, the high blood pressure during pregnancy, and its complications has significant role in maternal outcomes.2. Correlation between preeclampsia and maternal as well as perinatal outcomes was examined.3. Preeclampsia correlated significantly with delivery process, IUGR, LBW, and preterm birth, but not significantly with antepartum and postpartum hemorrhages, eclampsia, HELLP syndrome, maternal and perinatal mortality, as well as with neonatal asphyxia.   ABSTRACT Objectives: This research aimed to find correlation between preeclampsia and maternal as well as perinatal outcomes in Regional Public Hospital, Madiun, Indonesia, from 1 January 2017 to 30 September 2020. Materials and Methods: An observational analysis was applied in this study with a cross-sectional design. This study used secondary data from medical records of Regional Public Hospital, Madiun, Indonesia, with retrospective sampling and total sampling methods. Samples were 250 preeclamptic mothers with or without severe symptoms. Results: Of 250 preeclamptic mothers, only 216 samples could participate in this study. Maternal outcomes included spontaneous PV delivery (12.22%), SC (87.78%), antepartum hemorrhage (0.45%), postpartum hemorrhage (6.33%), eclampsia (0.45%), HELLP syndrome (0.90%), and maternal mortality (0.45%), while perinatal outcomes covered IUGR (7.69%), LBW (33.94%), preterm birth (12.67%), perinatal mortality (2.71%), and asphyxia neonatorum (13.12%). Conclusion: There was a significant correlation between preeclampsia with or without severe symptoms and maternal outcomes, which was the delivery process, and perinatal outcomes, which were the IUGR, LBW, and preterm birth. However, there was no significant correlation for antepartum hemorrhage, postpartum hemorrhage, eclampsia, HELLP syndrome, maternal mortality (maternal outcomes), perinatal mortality and neonatal asphyxia (perinatal outcomes).